GE_GERICHTE P/14803/2017 vom 22. März 2018 - GE Cour de justice (2018)
VOIES DE FAIT ; INTÉGRITÉ CORPORELLE ; DOL ÉVENTUEL ; NÉGLIGENCE ; ENLÈVEMENT(INFRACTION) ; CONTRAINTE(DROIT PÉNAL) | CP.126; CP.12.al1; CP.12.al3; CP.181; CP.183.ch1; CPP.126.al1.letb; CPP.428.al1